Prospective associations of social self-control with drug use among youth from regular and alternative high schools - Sun Ping; Rohrbach Louise; Sussman Steve; Pokhrel Pallav (BMC, 2007)
Abstract Background This study examined the one year prospective associations between adolescent social self-control and drug outcomes (cigarette use, alcohol use, marijuana use, hard drug use, and problem drug use) among adolescents from regular and continuation high schools. In our previous cross-sectional study, poor social self-control was found to be associated with higher drug use, controlling for 12 personality disorder categories. In this study, we attempted to find out (a) whether lack of social self-control predicted drug use one year later, and (b) whether drug use at baseline predicted social self-control one year later. Methods We surveyed 2081 older adolescents from 9 regular (N = 1529) and 9 continuation (alternative) (N = 552) high schools in the Los Angeles area. Data were collected at two time points in an interval of approximately 1 year. Results Past 30-day cigarette smoking, marijuana use, hard drug use, and problem drug use at baseline were found to predict lower social self-control at follow-up, controlling for baseline social self-control and demographic variables. The effect of problem drug use as a one-year predictor of social self-control was found to be moderated by school type (regular or continuation high school), such that the relationship was significant for continuation high school students only. Conversely, social self-control was found to predict past 30-day alcohol use, marijuana use, and problem drug use, controlling for baseline drug use and demographic variables. For alcohol use, marijuana use, and problem drug use outcomes, school type was not found to moderate the effects of social self-control, though an interaction effect was found regarding cigarette smoking. Social self-control was a significant predictor of cigarette use only at regular high school. Conclusion The results indicate that social self-control and drug use share a reciprocal relationship. Lack of social self-control in adolescents seems to result in increased drug use, which in turn is likely to further decrease social self-control. Thus, it seems that social self-control is an alterable cognitive-behavioral attribute which can be improved through skill-based interventions in order to prevent drug use among adolescents. Policies aimed at preventing drug abuse among adolescents may benefit from institutionalizing social self-control skills training.